DATA INVESTIGATION OF PK-LQP AIRPLANE VERTICAL DEVIATION USING CLASS 1 AND TIER 1 DATASETS - Rossi PASSARELLA; Siti NURMAINI; Muhammad Naufal RACHMATULLAH; Harumi VENY; Huda UBAYA; Firdaus FIRDAUS (Scientific Journal of Silesian University of Technology. Series Transport)
The vertical deviation is one of the important stages in commercial aircraft flights because indications of malfunction can be detected faster by the pilot rather than in other flight phases. The purpose of this study is to investigate whether the PK-LQP airplane experienced unusual altitude movements during the vertical deviation phase since the airplane taking off from Seattle (Boeing Manufacture's home base) until the airplane crash. The airplane, which is of the type B737 MAX8, had operated for 83 days, during which it completed 438 flights using a total of 107 flight codes, and it travelled to 36 airports. According to the findings of an investigation of the data, we found that only 69 (39%) were included in tier 1, which had an ADS-B data update interval message below 10 seconds, complying with ICAO and FAA-AVN standards. With this class 1 and tier 1 dataset, we conducted an EDA to find the data insight, which revealed that there was a disturbance in the speed and altitude indications on the airplane instrumentation, causing a misperception for the pilot and causing the airplane to drastically drop in altitude (more than 100 feet).